MOF encapsulated sub-nm Pd skin/Au nanoparticles as antenna-reactor plasmonic catalyst for light driven CO2 hydrogenation. (June 2021) - Zhang, Xibo; Fan, Yunyan; You, Enming; Li, Zexuan; Dong, Yongdi; Chen, Luning; Yang, Ye; Xie, Zhaoxiong; Kuang, Qin; Zheng, Lansun
Abstract: Activation of CO2 with plasmon induced hot electrons has attracted great attention due to its moderate reaction conditions, but high-efficiency plasmonic catalysts still remains challenging. Herein, we designedly prepared an antenna-reactor plasmonic catalyst with core-shell structure, i.e . sub-nm Pd skin/Au NPs encapsulated within UiO-66-NH2 (Au@Pd@UiO-66-NH2 -0.5) for CO2 hydrogenation under light-heat dual activation. Under the photo-thermal synergism, CO2 can be efficiently converted into CO and the optimal production rate reaches 3737 µmol/gmetal /h at 150 °C. Thereinto, ultrafast transient absorption spectroscopy reveals that the sub-nm Pd skin provides a longer time window for hot electron transfer and efficient retardation of energy dissipation. Theoretical calculations further confirm the significant reductions in HOMO-LUMO gap of CO2 and reaction energy barrier from CO2 * to COOH* through adsorption of CO2 on sub-nm Pd skin, promoting its efficiency and selectivity. Our findings provide new insights into design of bimetallic plasmonic catalysts for low-temperature catalysis. Graphical Abstract: A novel antenna-reactor plasmonic photocatalyst for light-driven CO2 hydrogenation were designedly synthesized. Strikingly, with sub-nm Pd skin/Au nanoparticles being encapsulated within amino-modified Zr(IV)-based MOF, CO2 can be selectively converted to CO with 100% efficiency. ga1 Highlights: UiO-66-NH2 encapsulated Au@Pd NPs was used for light driven CO2 hydrogenation. The sub-nm Pd skin delays the dissipation of energy gained from photon absorption. The Pd skin reduces the reaction energy barrier from CO2 * to COOH*.